Evaluation of educational strategy, grounded on problem-based learning on nursing undergraduate - Miriam Fernanda Sanches Alarcon; Kelly Holanda Prezotto (Universidade Federal do Ceará, 2016)
Objective: to compare the performance of student´s learning from evaluations of the method Problem-Based Learning and the Traditional method, in a discipline of undergraduate Nursing. Methods: an experimental study, performed with 16 students of the Degree course in Nursing. The experimental group was submitted to the educational strategy grounded on Problem-Based Learning and the control group to Traditional education. Cognitive Assessment Exercise evaluations were performed and traditional assessments for the two groups. Results: students in the experimental group showed better performance when compared to students from the traditional method. Conclusion: there was a positive influence on the strategy implemented for learning in Nursing, such as improved of critical thinking, knowledge construction.